¿Que nadie se quede atrás?: una mirada crítica a la territorialización de los ODS en los planes de desarrollo de tres municipios boyacenses (Colombia), 2016-2023 - Lyda Marcela Herrera-Camargo; César Nicandro Cruz-Rubio (Revista Iberoamericana de Estudios de Desarrollo)
The motto «Let no one behind» sums up the concept of sustainable and inclusive development that envisions 2030 Sustainable Development Goals (SDGs) Agenda. Localizing SDGs to the territory is a priority and at the same time complex task, in which each country has been confront with variable success rates, and where the proper design of the main planning instruments is a key task in this localization process. Local plans are conceived as policy designs; we analyze the design of six local development plans and strategic documents of three municipalities of Boyacá (Colombia) during 2016-2022. A critical debate is presented. Main findings show a great difficulty in assuming 2030 SDGs Agenda at design-content level, as well as persistent important structural challenges that reveals there is still a long way to go.